The Efforts to Improve Basic Writing Skills of 4-5 Year Old Children Through Rubber Seed Collage at TK Islam Al-Husein - Uyun, Fahrotul; Zahro, Ianatuz; Siswono, Hendrik (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to improve the basic writing skills of children aged 4-5 years through collage activities using rubber seeds at TK Islam Al-Husein. The research employs the Classroom Action Research (CAR) method using the Kemmis & McTaggart model, implemented in two cycles, each consisting of planning, implementation, observation, and reflection stages. The research subjects were 12 children from Group A, with data collection techniques involving observation, documentation, and informal interviews.The results show a significant increase from the pre-cycle to cycle II. In the pre-cycle, no children (0%) achieved the minimal